Pathogenicity variation and DNA polymorphism of Bipolaris sorokiniana infecting winter wheat in the Huanghuai floodplain of China. (8th October 2020) - Kang, Ruijiao; Hu, Yanfeng; Wang, Limin; Xie, Shunpei; Li, Yonghui; Yuan, Hongxia; Wang, Min; Chen, Linlin; Ding, Shengli; Li, Honglian
Abstract: Wheat root rot, caused by Bipolaris sorokiniana, has led to severe losses of wheat products worldwide. To evaluate the pathogenicity and genetic variation of B . sorokiniana, diseased wheat samples were collected from 97 locations in the Huanghuai floodplain of China in 2014 and 2015 for analysis. A total of 673 isolates were obtained, 262 of which were identified as B . sorokiniana . Pathogenicity analysis of the isolates revealed variation in pathogenicity, which was not directly correlated with geographic region. Large variations in pathogenicity were also found within geographic groups. To determine the genetic structure of the populations, PCR was performed with universal rice primers (URP). Cluster analysis based on amplification patterns showed that the classified groups were correlated with geographical regions. Thus, analysis of the genetic diversity of the population indicated a negative correlation with geographic origin, that is, the greater the distance between sites, the lower the genetic variation similarity coefficient. Identification of wheat germplasm resistance showed that resistant cultivars accounted for a low percentage, while susceptible and highly susceptible cultivars were in the majority. Overall, these results are meaningful for developing strategies to prevent and control wheat root rot. Abstract : We studied 262 isolates of Bipolaris sorokiniana among which pathogenicity variation was not correlated with geographic region, while genetic diversity indicated a negative correlation.